Italy : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Report on the Observance of Standards and Codes (ROSC) data module provides a review of Italy's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS), complemented by an in-depth assessment of the quality of national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics. The assessment reveals that Italy subscribes to the SDDS. It also meets the SDDS specifications for coverage, periodicity, and timeliness for all data categories (with two exceptions) and for advance release calendars.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet